Advances in Molecular Breeding Toward Drought and Salt Tolerant Crops - Jenks, Matthew A.; Hasegawa, Paul M.; Jain, Shri Mohan (Springer Netherlands : Imprint: Springer, 2007)
Plant stress caused by drought and salinity are among the major constraints on crop production and food security worldwide. Breeding programs to improve crop yield in dry and saline environments have progressed slowly due to our limited understanding of the underlying physiological, biochemical, developmental, and genetic mechanisms that determine plant responses to these forms of stress, as well as to technical difficulties in combining favorable alleles to create the improved high yielding genotypes needed for these environments. Advances in Molecular Breeding toward Drought and Salt Tolerant Crops seeks to integrate the most recent findings about key biological determinants of plant stress tolerance with modern crop improvement strategies. This volume is unique because is provides exceptionally wide coverage of current knowledge and expertise being applied in drought and salt tolerance research, spanning the scientific hierarchy from physiology, biochemistry, development, and genetics, to the newest technologies being used to manipulate drought and salinity associated traits for germplasm improvement. This book will be an invaluable reference for educators and researchers in agronomy and horticulture, crop breeding, molecular genetics, and biotechnology.